PENGARUH KOMPENSASI, TINGKAT PENDIDIKAN DAN KARAKTERISTIK INDIVIDU TERHADAP PRESTASI KERJA KARYAWAN - Hidayatullah, Farhan (Universitas Harapan Medan, 2025)
This study aims to determine the effect of compensation, educational level and individual characteristics on the work performance of employees of PT. Astra Internasional Tbk. – Toyota Sales Operation AUTO 2000 Cabang Sisingamangaraja Medan either partially or simultaneously. The population in this study amounted to 317 people, and using the Slovin formula obtained a sample of 104 people. The analysis technique used is multiple linear regression. The results showed that the style of compensation had a positive and significant effect on the work performance of the employees of PT. Astra Internasional Tbk. – Toyota Sales Operation AUTO 2000 Cabang Sisingamangaraja Medan. The level of education has a positive and significant effect on the work performance of employees at PT. Astra Internasional Tbk. – Toyota Sales Operation AUTO 2000 Cabang Sisingamangaraja Medan. Individual characteristics have no effect on employee performance at PT. Astra Internasional Tbk. – Toyota Sales Operation AUTO 2000 Cabang Sisingamangaraja Medan. Compensation, educational level and individual characteristics have a positive and significant effect on employee work performance at PT. Astra Internasional Tbk. – Toyota Sales Operation AUTO 2000 Cabang Sisingamangaraja Medan.